2014
DOI: 10.1111/jne.12175
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Early‐Life Adversity: Neurobiological, Behavioural and Epigenetic Adaptations

Abstract: During the perinatal period, the brain is particularly sensitive to remodelling by environmental factors. Adverse early-life experiences, such as stress exposure or suboptimal maternal care, can have long-lasting detrimental consequences for an individual. This phenomenon is often referred to as 'early-life programming' and is associated with an increased risk of disease. Typically, rodents exposed to prenatal stress or postnatal maternal deprivation display enhanced neuroendocrine responses to stress, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
227
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(243 citation statements)
references
References 202 publications
(281 reference statements)
11
227
0
5
Order By: Relevance
“…However, self-grooming can be seen as a de-arousing activity which is increased in anxious rats (Spruijt et al 1992;Kalueff and Tuohimaa 2005;Voigt et al 2005). Although the present design did not allow for analysing anxiety-related behaviour in dams, earlier studies demonstrated that offspring from dams previously exposed to a stress-inducing environment will show stronger responses to anxiogenic stimuli (Plotsky and Meaney 1993;Ladd et al 2000;Wei et al 2010;Maccari et al 2014;Barzegar et al 2015). Alternatively, grooming could also be associated with the significantly increased feeding as observed in the dams in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, self-grooming can be seen as a de-arousing activity which is increased in anxious rats (Spruijt et al 1992;Kalueff and Tuohimaa 2005;Voigt et al 2005). Although the present design did not allow for analysing anxiety-related behaviour in dams, earlier studies demonstrated that offspring from dams previously exposed to a stress-inducing environment will show stronger responses to anxiogenic stimuli (Plotsky and Meaney 1993;Ladd et al 2000;Wei et al 2010;Maccari et al 2014;Barzegar et al 2015). Alternatively, grooming could also be associated with the significantly increased feeding as observed in the dams in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Another important question is if the anxious phenotype will continue to exist into adult age, as early stressful experiences including lack of maternal care can "programme" anxiety (Weaver et al 2006;Seckl and Meaney 2006;Maccari et al 2014). This has not been addressed in this study though.…”
Section: Discussionmentioning
confidence: 99%
“…The intrauterine and early postnatal periods are characterized by high epigenetic plasticity (18); thus, as shown in laboratory rodents, early-life stress can affect development by durably imprinting specific brain regions and other tissues through epigenetic modifications (19). Restraint stress (20) or repeated exposure of pregnant dams to an aggressive congener (21), poor maternal care (22), or separation of recently born pups from the mother (23,24) were shown to result in tissue-specific changes in DNA methylation and in the activity of genes involved in the stress response (22)(23)(24)(25); some of these effects are sexually dimorphic (26). Epigenetics, however, is only one of the many effectors of early-life stress that can act on brain development (19); for example, prenatal stress in rats induces a reduction of neurogenesis in specific brain regions (27).…”
mentioning
confidence: 99%
“…Las estrategias terapéuticas encaminadas hacia el restablecimiento del equilibrio entre la neurotransmisión excitatoria e inhibitoria hipocámpica podrían ser eficaces en la corrección del fenotipo patológico causado por el EP 52 . La respuesta ante el estrés implica una reducción selectiva en la liberación de glutamato en el hipocampo ventral, relacionada con el comportamiento ansioso en modelos animales.…”
Section: Neurotransmisión Glutamatérgica En El Hipocampounclassified
“…Sin embargo, este efecto no se ha observado en el sexo femenino 57,58 . De este modo, respuestas diferenciales para cada sexo ante el EP han sido descritas (como lo señalado para los sistemas serotoninérgicos), lo que podría presentar una base fisiológica definida por el desarrollo intrauterino, puesto que en este período las hormonas sexuales juegan un rol central en la diferenciación de regiones cerebrales distintas para cada sexo 52 . Conjuntamente, una reciente investigación 11 evaluó por medio de resonancia magnética funcional a lactantes de seis meses de edad cuyas madres estuvieron deprimidas durante el embarazo.…”
Section: Ansiedad Depresión Y Amígdalaunclassified